What Difference Do Dividends Make?. Issue 6 (1st November 2016) - Conover, C. Mitchell; Jensen, Gerald R.; Simpson, Marc W.
Abstract : We evaluate the investment benefits of dividend-paying stocks and identify three major findings. First, high-dividend payers have the least risk yet return over 1.5% more per year than do nondividend payers. Second, the benefit of targeting dividend payers is conditional on investment style. Surprisingly, the benefit is largest for growth and small-cap stocks, the stocks of companies usually thought to benefit the most from reinvesting their cash flows. Third, long–short managers exploiting the value premium should focus on non-dividend-paying stocks as non-dividend-paying small-cap value stocks return 1% more per month than do non-dividend-paying small-cap growth stocks. Abstract : Editor's note: This article was reviewed and accepted by Robert Litterman, executive editor at the time the article was submitted.